INDUSTRIALISASI INDONESIA : KE MANA ?) - Pamungkas, Sri Bintang (Manajemen Bisnis Syariah, 2011)
China is always a super-power in the past as well as at present after World WarII ,one of the Veto Holder in the UN among other super-power such as United States ofAmerica, Rusia, Great Britain, and French.For some decade Cina was a closed behind“bamboo curtain” country under communism, but now Cina is open and shows itsmastery in industry and high tech including outer-space tercnology.The rise of China economy and industry gives competitive pressures especiallyin ASEAN countries which leads to the formation of CAFTA ( China ASEAN FreeTrade Area ). Meanwhile GATT (General Agreement on Tariff and Trade) which laterbecome WTO (World Trade Organization) for a more just international-global trade isstill far from successful. How is Indonesian industry so far in facing the competition ?Indonesia is a country rich of resource endowments with a big number ofpopulation as a human resource. Processing ang manufacturing industrieshavebeendeveloped since the Independence day of 1945 with an accelerating progressof manufacturing in the New Order beginning in 1967/1968. The import substitutionindustry for saving devisa and increasing employment opportunity is always inquestions and later increase the demand of export promotion especially for non-oiland gas commodities.The challenging gigantic growth of China should be responsed by a new systemand “new regime” which can face the challenge.Keywords: industrialization, economic cooperation, international trade, competition